The Handling of Uncertainty - Faust, Don (INTI Publishing House Sdn Bhd, 2005)
We argue that evidential logics based on a variety of non-classical frameworks, implementable with such machinery as extensions of logic programming and neural networks, will play an increasing role over the coming decades. These logic will provide frameworks for further improving both the intelligence of AT-related computer-based systems, and the fit of human discourse systems to the mainly evidential knowledge, which we most often have. Further, by increasingly adopting such evidential knowledge representation and processing frameworks, computer-based domains and human domains will come to increasingly share the same language and logic, which in turn will lead to substantial improvements in the problematic computer-human interface. Theories are nets cast to catch what we call “the world”: to rationalize, to explain, and to master it. We endeavor to make the mesh ever finer and finer. - Karl Popper, The Logic of Scientific Discovery, p.59